Novel T cell receptors reactive to the HPV16 E6 and E7 oncoproteins and strategy to potentiate their signaling strength using a co-stimulatory chimeric antigen receptor - Quirós Fernández, Isaac 1993- (Heidelberg, [Alemania], 2023)
More than 95% of all cervical cancer cases worldwide are caused by high-risk human papillomaviruses (HPV). The transformation and survival of the malignant HPV+ cells depend on the expression of the viral E6 and E7 oncoproteins, which makes them appropriate tumor-specific targets for immunotherapy. However, viral antigen presentation by tumor cells is generally low and limits the efficacy of tumor-reactive CD8+ T cells. In fact, adoptive cell therapies based on tumor-reactive T cell receptors (TCR) have shown limited efficacy as stand-alone treatments against solid tumors. In order to increase the efficacy of adoptive TCR-based immunotherapy of cancers caused by HPV16, a new strategy was devised combining an HPV16-specific TCR with a co-stimulatory chimeric antigen receptor (CAR). TCRs specific against the HPV16 E6 and E7 proteins were identified from the repertoire of healthy HLA-A2 donors and were characterized in terms of activation and cytotoxic capacity using the TCR-deficient Jurkat J76 cell line, and a novel NK-92-derived cell line capable of inducing TCR-mediated cytotoxicity. An E6-reactive TCR induced potent cytotoxicity towards HPV16+ cancer cell lines, while a TCR, reactive against the E7 protein showed weaker cytotoxicity against the HPV16+ cell lines tested. To enhance the specificity and signaling strength of the NK-92/TCR cells, a co-stimulatory CAR directed against the trophoblast cell surface antigen 2 (TROP2) was designed, carrying exclusively the intracellular domain of the inducible T cell co-stimulator protein (ICOS). NK-92 cells with co-expression of the E7-reactive TCR and the co-stimulatory CAR showed enhanced cytotoxicity against the HPV16+ and TROP2+ cancer cell lines. Overall, the data shows that a co-stimulatory TROP2-CAR can synergize with a tumor-specific TCR in NK-92 cells, enhancing their signaling strength and antigen-specific cytotoxicity. Such combination approach can help improve the efficacy of TCR-based adoptive...
Eine Gruppe von Alpha-Human-Papillomavirus (HPV)-Typen, die so genannten Hochrisiko-HPV, sind Erreger von Gebärmutterhals-, Anogenital- sowie Kopf- und Halskrebs. Die Krebsentstehung und -progression wird durch eine deregulierte Expression der viralen Onkoproteine E6 und E7 verursacht, was sie zu geeigneten tumorspezifischen Zielen für die Immuntherapie macht. Die virale Antigenpräsentation durch Tumorzellen ist jedoch im Allgemeinen gering und schränkt die Wirksamkeit von tumorreaktiven CD8+ T-Zellen ein. Adoptive Zelltherapien, die auf tumorreaktiven T-Zell-Rezeptoren (TCR) beruhen, haben sich als eigenständige Behandlungen gegen solide Tumore als wenig wirksam erwiesen. Um die Wirksamkeit der adoptiven TCR-basierten Immuntherapie von Krebserkrankungen, die durch HPV16 verursacht werden, zu erhöhen, wurde in dieser Studie eine neue Strategie entwickelt, die einen HPV16-spezifischen TCR mit einem co-stimulatorischen chimären Antigenrezeptor (CAR) kombiniert. TCRs, die gegen die HPV16- E6 und E7 Proteine spezifisch sind, wurden aus dem Repertoire gesunder HLA-A2-Spender identifiziert und hinsichtlich ihrer Aktivierung und zytotoxischen Kapazität unter Verwendung der TCR-defizienten Jurkat J76-Zelllinie und einer modifizierter NK-92-Zelllinie, die TCR-vermittelte Zytotoxizität induzieren kann, charakterisiert. Ein E6-reaktiver TCR induzierte eine starke Zytotoxizität gegenüber HPV16+ Krebszelllinien, während ein TCR, der gegen das E7-Protein reaktiv ist, eine schwächere Zytotoxizität gegenüber den getesteten HPV16+-Zelllinien zeigte. Um die Spezifität und Signalstärke der NK-92/TCR-Zellen zu erhöhen, wurde ein co-stimulatorischer CAR entwickelt, der gegen das Trophoblastenzelloberflächenantigen 2 (TROP2) gerichtet ist, das ausschließlich die intrazelluläre Domäne des induzierbaren T-Zell-Co-Stimulatorproteins (ICOS) trägt. NK-92-Zellen mit Co-expression des E7-reaktiven TCR und des co-stimulatorischen CAR zeigten eine erhöhte...
Dissertation (doctoral)--University Heidelberg. Facultaty of Mathematics, Engineering and Natural Sciences, 2023
Se considera un Trabajo Final de Graduación del Sistema de Estudios de Posgrado, según oficio no. OAICE-170-2025
Keywords: LINFOCITOS T -- RECEPTORES; CUELLO UTERINO -- CANCER; PAPILOMA; CANCER -- INMUNOTERAPIA; TERAPIA CELULAR; PROTEINAS TUMORALES